Influence of Nitrogen Levels and Weed Management Practices on Yield and Quality of Forage Pearl Millet (Pennisetum glaucum L.) - Choudhary, Sunita; Chopra, Neelam K.; Chopra, Nisha K.; Singh, Magan; Kumar, Rakesh; Kushwaha, Manish (Indian Journal of Animal Nutrition, 2017)
A field experiment was conducted using split plot design consisting of 4 nitrogen levels (0, 50, 100 and 150 kg N/ha) and 6 weed management practices (W1- pendimethalin application @ 1.0 kg a.i./ha pre-emergence (PE) + 1 hand weeding (HW) at 25 DAS, W2- atrazine application @ 0.75 kg a.i./ha PE + 1 HW at 25 DAS,W3- pendimethalin application @ 1.0 kg a.i./ha PE + halosulfuron application @ 67.5 g a.i./ha post emergence (POE) at 25 DAS, W4- atrazine application @ 0.75 kg a.i./ha PE + halosulfuron application @ 67.5 g a.i./ha POE at 25 DAS, weedy check and weed free) with three replications during kharif season of 2015 to evaluate the effect of nitrogen and weed management on yield and quality of forage pearl millet var. HC-20. The plant height (cm), leaves/plant, tillers/plant, green and dry fodder yield/ The CP and EE contents increased (P<0.05) with increase in level of N up to application of 100 kg N/ha. In contrast, the values of NDF, ADF and total CHO decreased with increase in nitrogen level and the highest values of these parameters were recorded in control plot. The application of atrazine @ 0.75 + halosulfuron @ 67.5 g a.i./ha yielded higher total-CHO compared to other treatments. The application of pendimethalin + 1 HW showed higher (P<0.05) plant height, green forage yield and EE over weedy check and remained at par with other treatments. Similarly, pendimethalin + 1 HW application resulted in higher CP and total ash over all treatments except weed free one.